The Influence of Technology Determinism and Technology Literacy on Student Learning Outcomes (On MA Daarul Hikmah Pamulang) - Kharisma Danang Yuangga; Jasmani Jasmani; Denok Sunarsi (PINISI Discretion Review, 2017)
The latest technological developments cause impacts in all fields. One of them is a change in social behavior. The purpose of this study is to determine technological determinism and technological literacy on student learning outcomes at MA Daarul Hikmah Pamulang. The method used is descriptive method with an associative approach. The sampling technique used was proportional random sampling using the method of saturated sampling technique with a sample of 78 respondents. The analysis tool uses validity test, reliability test, classic assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are technological determinism that has a positive and significant effect on student learning outcomes by 38.6%. Hypothesis testing is obtained tcount> ttable or (6.907> 1.992), so H0 is rejected and H1 is accepted meaning there is a positive and significant influence between technological determinism on student learning outcomes at the MA Daarul Hikmah Pamulang Office. Technology literacy has a positive and significant effect on student learning outcomes by 39.8%. Hypothesis testing is obtained tcount> ttable or (7.091> 1.992) so that H0 is rejected and H2 is accepted meaning that there is a positive and significant influence between technology literacy on student learning outcomes. A simultaneous test of technological determinism and technological literacy has a positive and significant effect on student learning outcomes with an influence contribution of 48.4%, while the remaining 51.9% is influenced by other factors. Hypothesis testing obtained the value of Fcount> Ftable or (40.435> 2.730), thus Ho is rejected and H3 is accepted. This means that there is a positive and significant effect simultaneously between technological determinism and technology literacy on student learning outcomes in MA Daarul Hikmah Pamulang